2018
DOI: 10.1016/j.xphs.2017.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Biorelevant Media Slows the Solution-Mediated Phase Transformation of Amorphous Spironolactone

Abstract: Solution-mediated phase transformation (SMPT) can reduce the high drug concentration expected from amorphous formulations, eliminating the improvement in drug absorption one hoped to gain from this high energy drug state. The differences in SMPT of a supersaturating system were compared in biorelevant media (fasted state simulated intestinal fluid and fed state simulated intestinal fluid) and United States Pharmacopeia compendial medium, simulated intestinal fluid without pancreatin. Amorphous spironolactone u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…In a previously published report, SPIR was raised to 214 C-217 C for 3 min with less than 0.5% degradation. 34 Thus, the degradation during the present DSC measurement was not significant.…”
Section: Thermal Property Measurementmentioning
confidence: 63%
See 2 more Smart Citations
“…In a previously published report, SPIR was raised to 214 C-217 C for 3 min with less than 0.5% degradation. 34 Thus, the degradation during the present DSC measurement was not significant.…”
Section: Thermal Property Measurementmentioning
confidence: 63%
“…The cooled material was ground in a mortar and passed through a 100 mm sieve in a glove bag at 3% relative humidity (% RH). Amorphous SPIR was prepared by spray drying as described by Kleppe et al 34 The amorphous nature was confirmed by the absence of birefringence under polarized light at 20X magnification, and the presence of a halo with no peaks by powder X-ray diffraction amorphous samples were stored in vials with a dry air headspace at À20 C.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on single-crystal X-ray diffraction and thermogravimetric analysis, SP incorporates 1/3 water into its crystal lattice . This new crystal form and polymorphism of spironolactone are still actively studied because of its variety, scientific relevance, and the importance as a worldwide-known API. , …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Phase changes can also occur during dissolution by a solution-mediated transformation of the metastable or unstable form of a compound to a more stable form or hydrates. 6e8 For example, Kleppe et al 8 showed that solution-mediated phase transformation of amorphous spironolactone to a hydrate resulted in decreased dissolution rates, which depended on the dissolution media. Differences in solubility and dissolution rate among polymorphs may have a significant impact on pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%